Lenguaje de los pájaros e idea de la poesía - Fabre, Daniel (Revista de Antropología Social, 2008)
This text explores the relation of songs of birds with the virile development of young men and poetry in the European cultural space both from the Middle Ages, through the songs of troubadours, as well as from the rural contemporary World. The article also considers how the great majority of famous societies bring birds to a particular competence in amorous relationship, either erotic or sentimental, and how this supposed knowledge feeds the illustrated expression and the poetics creations which have love as reference. The article argues that, in order for the universe of birds to become the unexhaustable reserve of metaphors for love and furthermore, for the proximity of both sexes, it’s necessary for the doing to become what’s said, that it acquires the symbolic competence from which poetry is the refined point. - L’article interroge sur le rapport entre le chant des oiseaux et la formation virile des garçons et la poésie à l’intérieur de l’espace cultural européen, aussi bien au Moyen Age, par les chansons des troubadours, que dans des univers ruraux contemporains. De plus, l’article pose comment la plupart des sociétés connues prêtent aux oiseaux une competénce particulière en matière des relations amoureuses, qu’elles soient érotiques ou sentimentales, et que ce savoir supposé nourrit les expressions imagées et les créations poétiques qui ont l’amour pour sujet. L’article insiste aussi sur ce point, pour que l’univers des oiseaux devienne le réservoir inépuisable des métaphores de l’amour, et donc du rapprochement des deux sexes, il faut que le faire devienne un dire, que soit acquise la compétence symbolique dont la poésie est la pointe raffinée.